ナンキョク ヨウ テイ ショウヒ デンリョク データ シュウロク キ ノ カイハツ - 勝田, 豊; カツタ, ユタカ; 寺井, 啓; テライ, ケイ; Katsuta, Yutaka; Terai, Kei (1986)
P(論文) 国立極地研究所極地設営工学研究グループでは, 南極における無人観測システムの基礎的な知識・技術を得るために「自然エネルギーを動力とした無人観測システムの開発」計画(昭和57-59年度)を実施した。その計画の一部として, サンプリング間隔の長い非連続データを対象にしたデータ収録器を開発した。無人観測の性格上, 現場で十分な電力を確保することは難しいので開発の重点を低消費電力化に置き, かつ長期のデータ収録を目標にして開発を進めた。その結果, JARE-26でテストランを行い良好な成果を得, JARE-27で実用観測を開始するに至った。 A project of the "Development of Unmanned Observation System Utilizing Natural Energy" was carried out by the Polar Regions Engineering Department, National Institute of Polar Research to obtain fundamental knowledge and technique of unmanned observation systems in Antarctica during 1982 to 1984. A data logger for discontinuity data of long time range was developed as a part of the project. On the development of the data logger, it is required to achieve very low consumption of electricity and long-term recording period because it is very difficult to obtain large electric power constantly. A new data logger system has been designed and tested in Antarctica. Good results have been obtained by the experiments during the 26th and 27th Japanese Antarctic Research Expedition (1984-1986). departmental bulletin paper